1983
DOI: 10.1002/ajh.2830150102
|View full text |Cite
|
Sign up to set email alerts
|

Impaired pentose phosphate shunt function in sickle cell disease: A potential mechanism for increased heinz body formation and membrane lipid peroxidation

Abstract: The red cells' antioxidant defense mechanisms were compared between individuals with sickle cell disease and those with hemolytic anemia and reticulocytosis. In sickle cell disease, there was a significant increase in incubated Heinz body formation (p less than .001), a decrease in reduced glutathione concentration (p less than .01), an increase in glucose-6-phosphate dehydrogenase activity (p less than .01), and a decrease in glutathione reductase activity (p less than .005). The patients with sickle cell dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 27 publications
4
29
0
Order By: Relevance
“…Previous studies have described impaired antioxidative mechanisms in sickle RBCs (35,36) and oxidative membrane damage reflected in the presence of oxidized protein thiols (12), but affected proteins have not been identified. The transfer of NO from SNO-Hb to CDAE1 requires close apposition of a ␤-Cys-93 thiol to cysteine thiol within CDAE1, and bound AE1 and HbA (or SNO-HbA) can in fact be disulfide-linked by oxidative (Cu 2ϩ ) catalysis (3).…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have described impaired antioxidative mechanisms in sickle RBCs (35,36) and oxidative membrane damage reflected in the presence of oxidized protein thiols (12), but affected proteins have not been identified. The transfer of NO from SNO-Hb to CDAE1 requires close apposition of a ␤-Cys-93 thiol to cysteine thiol within CDAE1, and bound AE1 and HbA (or SNO-HbA) can in fact be disulfide-linked by oxidative (Cu 2ϩ ) catalysis (3).…”
Section: Resultsmentioning
confidence: 98%
“…27 KCC activation and cellular dehydration have also been demonstrated in human (SS) RBCs in association with almost complete (nonoxidative) GSH depletion induced by CDNB. 24,25,46 However, it is noteworthy that previous studies found glutathione levels in SS RBCs to be only 15% less than in AA RBCs, 47,48 whereas lowering of GSH levels by 80% was required for KCC activation in sheep and dog RBCs. 26,27 In addition, CDNB treatment resulted in loss of the volume response in these cell, 25 which is not consistent with the normal volume response in SS RBCs ( Figure 1C) reported in this study.…”
Section: Discussionmentioning
confidence: 97%
“…[19][20][21][22][23][24][25][26] Sickle erythrocytes have a shortened survival time and are more susceptible to oxidant damage than red blood cells from healthy individuals. [27][28][29][30][31] Many of the alterations in the redox environment known to occur in SCD can impact global GSH homeostasis, including decreased enzymatic activity of glutathione peroxidase, 27,28 catalase 28 and GSH reductase, [15][16][17]32 impaired pentose phosphate shunt activity, 32 increased superoxide and free radical generation, 16,29,[33][34][35][36][37] decreased NO bioavailability, 20,21,23, [38][39][40][41][42][43][44][45] and decreased NAD redox potential. 46,47 Recently, erythrocyte GSH depletion has been linked to hemolysis, suggesting a direct role in erythrocyte viability.…”
Section: Introductionmentioning
confidence: 99%